Whose growth in whose planetary boundaries? Decolonising planetary justice in the Anthropocene - Farhana Sultana (Geo: Geography and Environment, 2023)
Abstract This critical analysis examines the geopolitics of planetary environmental injustice and the imperative for systems change to address the intertwined crises of climate breakdown and unsustainable economic growth. Climate breakdown has heightened attention to uneven anthropogenic use and abuse of the planet's biosphere and common pool resources. Recent arguments by climate scholars suggest that various planetary boundaries have already been breached, resulting in dramatic and harmful socio‐ecological consequences. These trends raise crucial questions of equity and justice, especially concerning responsibilities and impacts. By centring Global South perspectives, prevailing ideologies promoting hyperconsumption, overproduction and waste are interrogated. The incommensurability of socioecological justice with ongoing unsustainable extractive and exploitative economic growth paradigms, which contribute to further transgressions of planetary boundaries, underscore the urgency of decolonising underlying colonial‐capitalist ideologies and practices. This entails a fundamental reformulation of paradigms to envision a more just and sustainable future, one that dismantles oppressive systems and advances justice‐oriented praxis.